PERAN KEPEMIMPINAN LURAH DALAM MENINGKATKAN KINERJA PEGAWAI DI KANTOR LURAH WUNDUDOPI KECAMATAN BARUGA KOTA KENDARI - Yunitawati Lampasa; Riston G Ahmad (Journal Publicuho, 2024)
This research aims to determine the role of Village Head Leadership in improving employee performance at the Wundudopi Village Head Office, Baruga District, Kendari City. The research method used is descriptive qualitative. Data was obtained from direct interviews with Wundudopi employees and village heads. The research results show that as a leader, the Wundudopi Village Head has played a very important role in improving employee performance.